2022
DOI: 10.2174/1573413717666210531153107
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of Super-Paramagnetic Iron Oxide Nanoparticles (SPIONs) for Minimising Aeromonas hydrophila Load from Freshwater

Abstract: Background: The current study was conducted to prepare an efficient super-paramagnetic iron oxide nanoparticle (SPIONs) to remove Aeromonas hydrophila from water. Methods: The nanoparticles were synthesized by the co-precipitation method and characterized by DLS, UV-Vis spectrophotometer, FT-IR, XRD, FEG-TEM, and VSM analysis. Results and Discussion: The results showed that the synthesized SPIONs were having a size range of 8-12nm with magnetic property. Bacteria removal efficiency and antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 86 publications
6
10
0
Order By: Relevance
“…The B-SPIONs showed the UV-Vis spectra between 225 and 250 nm agreed with the findings ofSamrot et al (2017) andSamrot et al (2018). Our previous study observed the B-SPIONs absorption peak at 229 nm(Kumar et al, 2021). In the present study, the absorption peak of G-SPIONs appears at 239 nm, which is typical for glucose-conjugated IONPs.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…The B-SPIONs showed the UV-Vis spectra between 225 and 250 nm agreed with the findings ofSamrot et al (2017) andSamrot et al (2018). Our previous study observed the B-SPIONs absorption peak at 229 nm(Kumar et al, 2021). In the present study, the absorption peak of G-SPIONs appears at 239 nm, which is typical for glucose-conjugated IONPs.…”
supporting
confidence: 89%
“…FT-IR was performed to confirm the functional groups on the surface of the synthesized materials (Shameer & Nishath, 2019). The FT-IR spectrum and absorption bands of synthesized G-SPIONs were observed in the 450-4,000 cm À1 wavenumber range, as shown in 2017), while another one peak was appeared at 815.84 cm À1 suggested that there must be strong vibrational interaction between SPIONs and glucose (Sivakumar et al, 2017). Altogether, results further confirm that the surface of bare SPIONs has been conjugated with glucose.…”
Section: Ft-ir Analysissupporting
confidence: 64%
See 3 more Smart Citations